2017
DOI: 10.5414/cn109216
|View full text |Cite
|
Sign up to set email alerts
|

Predicting augmented renal clearance using estimated glomerular filtration rate in critically-ill children

Abstract: The eGFR correlates with the VTL, and the eGFR cutoff value can predict a subtherapeutic vancomycin level. eGFR is a reliable and efficient alternative to mGFR for identifying ARC.
.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Review of titles and abstracts led to the retrieval of 215 potentially relevant full‐text citations. After full‐text review, 25 citations met the criteria for inclusion 16–41 . The most common reason for exclusion was non‐pediatric population studies (190 citations), followed by lack of ARC data (24 citations).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Review of titles and abstracts led to the retrieval of 215 potentially relevant full‐text citations. After full‐text review, 25 citations met the criteria for inclusion 16–41 . The most common reason for exclusion was non‐pediatric population studies (190 citations), followed by lack of ARC data (24 citations).…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 summarizes the characteristics of the studies included based upon their primary objective 16–41 . The first articles related to ARC in pediatrics were published in 2015 and were pharmacokinetic objective studies 20,36 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As eGFR values differ according to the formula, the ARC varies similarly. Paediatric literature indicates that values vary between 12 and 75% 25,34–36 . All of these studies used the Schwartz formula.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also reported subtherapeutic vancomycin exposure in critically ill children with ARC [52,56,64,[111][112][113][114][115]. Increased loading or initial doses have been recommended to achieve early therapeutic exposure.…”
Section: Subpopulations Of Critically Ill Children and Neonates At Increased Risk Of Pharmacokinetic Alterations 41 Augmented Renal Clearmentioning
confidence: 99%